Effect of aging on 24-hour pattern of stress hormones and leptin in rats - Cano, Pilar (2008)
This work analyzes the 24-hour changes of hypothalamic–pituitary–adrenal (HPA) axis activity and leptin release in aged rats. Three- and 22-month-old male Wistar rats were killed at 6 time intervals during a 24- hour cycle (n= 8–10 rats/group). Aging augmented plasma ACTH while it decreased plasma and adrenal gland corticosterone levels. Plasma and adrenal corticosterone levels attained high levels during all the scotophase, concomitantly with the maxima in ACTH levels, whereas in aged rats only a brief plasma corticosterone peak at the early scotophase and no time of day variations of adrenal corticosterone were observed. Aging augmented circulating leptin, with a significant interaction “age × time” in the factorial ANOVA, i.e. only in young rats time of day changes were significant, with the lowest values of leptin at the middle of the light period and higher values at night. When plasma leptin was expressed on body weight basis, the age-related differences became not significant but the daily pattern of plasma leptin found in young rats persisted. Plasma and adrenal corticosterone levels correlated significantly with plasma ACTH only in young rats. Likewise, plasma leptin correlated with plasma corticosterone only in young rats. These changes can be attributed to a disrupting effect of aging on the homeostatic mechanisms modulating HPA activity and leptin release.